Yelling into the Silence and its Echos. Czech Shoah Poetry Written till 1960s and its Reception - Balík, Štěpán (Poznańskie Studia Slawistyczne, 2017)
The literary reflection of the Shoah in Czech war and post-war poetry is very limited. Only a few non-Jewish poets have ever returned to thistheme (e.g. František Halas,Jiří Kolář,Jaroslav Seifert, Jan Skácel, Karel Křepelka, Radek Malý). Additionally, literary “testaments” of Jewish authors (Karel Fleischmann, Pavel Friedmann etc.) resulted in only two collections of poems entirely dedicated to the suffering of the Jews during the Nazi oppression (Ota Reich and Michal Flach). On the other hand, there are several books of poetry about Lidice and suffering of the Czech people during the World War II by Viktor Fischl, Karel Šiktanc, Libuše Hájková, Miloš Vacík and others. After the war there were only Jaroslav Seifert and Jiří Kolář among well-known poets who refered to the Shoah in a more significant way. Seifert created a figure of a Jewish girl, Hendele, in his collection of poems Koncert na ostrově (Concert on the Island), which develops the literary narration of the Shoah. Jiří Kolář referred to the Shoah repeatedly, however, he only had a limited chance to publish his work. As a result of this fact, the reception of Czech post-war poetry about the Shoah is almost absent. In my article, I concentrated on some reviewers’ remarks that have already been published since the war-time and other reflections of this kind such as editions of books by Jiří Orten, Hanuš Bonn, Jiří Daniel. A hypothetical reaction on the Shoah verses by Pick’s cabaret audience or Halas’s anonymous poetic obituary paying tribute to Jiří Orten are rather specific sorts of reception. The critical reflection of Kolář’s work in the context of the mass murder commited during the WW II is exceptional. However, the specific motifs of the Shoah were significantly focused on only in recent years by three foreign reviewers (Leszek Engelking, Hanna Marciniak and Anja Golebiowski). Czech Shoah poems printed or reprinted in Jewish periodicals (e.g. annual “Židovská ročenka”, published since 1954) represent a commemorative function, even though sometimes with informative commentaries. They miss any analytical aspect.